Development of a low-cost educational liquid-level sensor circuit. Issue 2 (April 2015) - Ibrahim, Dogan
In this article, the design of a low-cost educational liquid-level sensor circuit is described. The sensor is of capacitive type and is in the form of a parallel plate capacitor made up of two aluminium foil papers stuck on opposite sides of the container whose liquid level is to be measured. The sensor works on the principle that its capacitance changes with the level of liquid in the container as a result of the change in permittivity between the plates. Thus, by calculating the capacitor value, one can calculate the level of the liquid in the vessel. In this article, the capacitor value is calculated using a microcontroller-based circuit where an RC circuit is formed and the rise-time of the voltage across the capacitor is measured and is then related to the level of the liquid. The results are found to have good linearity and repeatability, and it is shown that the liquid level can be measured accurately and with low cost using some readily available basic components.